Effect of sodium bicarbonate on Candida albicans adherence to thermally activated acrylic resin - Fernando Augusto Cervantes Garcia de Sousa; Thaís Cachuté Paradella; Cristiane Yumi Koga-Ito; Antonio Olavo Cardoso Jorge (Sociedade Brasileira de Pesquisa Odontológica, 2009)
The purpose of this study was to evaluate the effect of 5% sodium bicarbonate on the adherence of Candida albicans to thermally activated acrylic resin. Fifty 4 mm² specimens of acrylic resin were obtained using a metallic matrix. The specimens received chemical polishing, were sterilized and then immersed in Sabouraud broth, inoculated with Candida albicans standardized suspension. After 24 hours of incubation at 37ºC, the specimens were divided into four groups according to the substance used for disinfection (5% sodium bicarbonate, 0.12% digluconate chlorhexidine, vinegar and Corega Tabs). A control group was included, in which distilled water was used. The adhered microorganisms were dispersed, diluted and plated onto culture media to determine the number of colony-forming units (cfu/mL). The results were analyzed through the Mann-Whitney statistical test at the 5% level of significance. Only 0.12% digluconate chlorhexidine and 5% sodium bicarbonate presented a statistically significant difference (p = 0.0010 and p = 0.0156, respectively) compared to the control group, decreasing the number of cfu/mL. However, when the different disinfecting solutions were compared with each other, only 0.12% digluconate chlorhexidine presented a statistically significant difference in the reduction of cfu/mL. It was concluded that although 0.12% digluconate chlorhexidine was more effective in the reduction of Candida albicans adherence values to thermally activated acrylic resin, 5% sodium bicarbonate also proved to be a viable alternative.